Pengaruh Literasi Keuangan, Kepercayaan, dan Risiko terhadap Minat Menggunakan Pinjaman Online : Studi Kasus Pada Mahasiswa PTN dan PTS di Kota Semarang - Naufal Muflih Banyu Aji; Batara Daniel Bagana (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to analyze the influence of financial literacy, trust and risk on interest in using online loans. This study employs a quantitative approach. Participants in this study were students from Semarang City's PTN and PTS programs. Data collected by administering questionnaires and utilizing a purposive sampling technique with a sample size of 65 respondents. Hypothesis testing and multiple linear regression are tools used in data analysis. The research results show that financial literacy and trust have no effect on interest in using online loans, while risk has a positive effect on interest in using online loans, with a contribution of 13.8%. In conclusion, literacy and trust have no effect, while risk has a positive effect on interest in using online loans. Keywords: Financial Literacy, Online Loans, Risk, Trust